Building a SharePoint 2016 Home Lab A How-To Reference on Simulating a Realistic SharePoint Testing Environment - Simpkins, Stacy (Apress : Imprint: Apress, 2016)
This book is a step-by-step guide to building your own SharePoint farm in a home lab setting. Learn how to build a windows domain and then join servers into the domain in order to create your own testing and learning environment. After you get the domain stood up, where you go from there is up to you. This book will help you learn how to spin up SharePoint in a least privileged fashion. This isn't strictly a SharePoint book, though. For example, if you're not a SharePoint professional and are just looking to create a working windows domain for other purposes; the home-lab domain that you'll create will work great for Exam preparation for non-SharePoint purposes. You could even use it for learning how to install Exchange Server. After all, it's your Home Lab domain. In this book you will build your home-lab domain and you'll have a great place for learning how to administer SharePoint and develop SharePoint Apps. Here are just some of the tasks you'll complete in easy to follow exercises: Create a windows domain and a certificate authority, so that you can run SharePoint on SSL Join servers to the domain and configure other technology on the member servers as needed Install SQL Server, and correctly partition the server in accordance with best practices Install and configure a SharePoint farm Spin up Host Named Site Collections (HNSC's) Install and configure Visual Studio Who This Book Is For: This book is suitable for both developers and administrators. No technical knowledge is assumed beyond a general familiarity with computers and computing terminology. The resulting domain will be suitable for both IT and developer testing needs. .